MENGEMAS KESENIAN TRADISIONAL MELALUI STASIUN TELEVISI SWASTA DI INDONESIA - Tanudjaja, Bing Bedjo (Institute of Research and Community Outreach - Petra Christian University, 2006)
There is an incompletion in a traditional art performance when using communication media such as television compared to being present in the event. They are missing some non verbal nuances%2C like the body language%2C face expressions%2C etcetera%2C that would help in deeply understanding word meanings.The concept of